Analisis Komunikasi Internal Badan Gizi Nasional Pada Bidang Pemantauan Dan Pengawasan Dapur MBG - Hera Cahya Ananda; Juandanilsyah (Jurnal Komunikasi dan Ilmu Sosial, 2026)
This study aims to analyze internal communication in the monitoring and supervision division of the Makan Bergizi (MBG) kitchen program at the National Nutrition Agency. The focus of this research is to examine the internal communication process among cross-agency employees, the forms of formal and informal communication, communication barriers, and efforts to overcome these barriers. This study uses a qualitative approach with data collection methods including interviews, observation, and documentation. The informants consist of employees from the National Nutrition Agency, the Ministry of Defense, as well as administrative and technical teams involved in the MBG kitchen supervision activities. The results show that internal communication is conducted through formal communication such as briefings, coordination meetings, work reports, as well as informal communication through direct interaction and digital media such as WhatsApp and email. Internal communication is influenced by differences in organizational culture across institutions, which affect communication patterns and work coordination. Communication barriers found include differences in task understanding, differences in work culture, and dynamic field conditions. Efforts to overcome these barriers are carried out through routine briefings, open communication, joint evaluation, and adaptation of work culture among employees. In conclusion, internal communication in the MBG kitchen monitoring and supervision division has been relatively effective in supporting cross-agency coordination, although several barriers still exist and need to be continuously improved through better communication and cultural adaptation.